2018
DOI: 10.3389/fmars.2018.00141
|View full text |Cite
|
Sign up to set email alerts
|

Spread, Behavior, and Ecosystem Consequences of Conventional Munitions Compounds in Coastal Marine Waters

Abstract: Coastal marine environments are contaminated globally with a vast quantity of unexploded ordnance and munitions from intentional disposal. These munitions contain organic explosive compounds as well as a variety of metals, and represent point sources of chemical pollution to marine waters. Most underwater munitions originate from World Wars at the beginning of the twentieth century, and metal munitions housings have been impacted by extensive corrosion over the course of the following decades. As a result, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
57
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(69 citation statements)
references
References 238 publications
(364 reference statements)
1
57
0
3
Order By: Relevance
“…However, maximum RDX and TNT concentrations in the flume water were lower than these highest attainable levels, consistent with the observation of low loss of Composition B mass at experiment termination (see Composition B fragments mass loss section). Therefore, the low maximum average concentration observed is not related to saturation because the maximum attainable dissolved concentrations in the flume and in the aforementioned aquaria experiments are significantly lower than the solubility limits for RDX and TNT (Beck et al ). Although a determination of why increasing concentrations tend to plateau is outside the scope of the present study, our hypothesis is that the observed behavior is likely related to decreases in the availability of water‐accessible MC at the Composition B surface.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…However, maximum RDX and TNT concentrations in the flume water were lower than these highest attainable levels, consistent with the observation of low loss of Composition B mass at experiment termination (see Composition B fragments mass loss section). Therefore, the low maximum average concentration observed is not related to saturation because the maximum attainable dissolved concentrations in the flume and in the aforementioned aquaria experiments are significantly lower than the solubility limits for RDX and TNT (Beck et al ). Although a determination of why increasing concentrations tend to plateau is outside the scope of the present study, our hypothesis is that the observed behavior is likely related to decreases in the availability of water‐accessible MC at the Composition B surface.…”
Section: Resultsmentioning
confidence: 88%
“…Underwater sites around the world are known to contain underwater military munitions (UWMM) as a result of military activities or historic disposal events. Munitions constituents (MC) including 2,4,6‐trinitrotoluene (TNT) and 1,3,5‐trinitro‐1,3,5‐triazine (RDX) may be released into the surrounding aquatic environments as a result of UWMM corrosion and breaching of the munition's outer casing (Lewis et al ; Rosen and Lotufo ; Wang et al ; Li et al ; Voie and Mariussen ; Rosen et al ; Beck et al ). Release may also occur from fragments of explosives formulations that become exposed following low‐order (incomplete) detonations resulting in fully breached munitions (Beck et al ).…”
Section: Introductionmentioning
confidence: 99%
“…The major transformation pathways of 2,4,6-trinitrotoluene (TNT) released into the environment include microbial reduction, metal catalyzed abiotic reduction, and photolysis, depending on the individual soil, sediment, or aquatic matrix [1–15]. TNT is also susceptible to alkaline hydrolysis, but the conditions of pH ≥ 9 required for significant hydrolysis to occur are not relevant to most environments.…”
Section: Introductionmentioning
confidence: 99%
“…Where TNT reaches the photic zone in surface waters or where light intensity is adequate, it may be assumed that photolysis takes place. Studies have detected TNT in surrounding sediments or in the water column derived from underwater unexploded ordnance [1, 12, 2932].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, another issue resulting from military activities in coastal marine environments is the intentional disposal of unexploded ordnance and munitions that contain organic explosives and a variety of metals. These can be assessed by RS technologies (USV and UUV) using Multibeam sonar, sub-bottom profiling, and magnetometry [132].…”
Section: Militarymentioning
confidence: 99%